Time Dependent S-brane Solutions in Five Dimensional Supergravity - F.P. Zen; Arianto Arianto; B.E. Gunara (Institut Teknologi Bandung, 2004)
We study time dependent S-brane solutions in gauged and ungauged supergravities in five dimensions. We find that the solutions have a close relationship with black holes and can be obtained by an analytic continuation from static black hole solutions.